Molecular characterization and drug resistance of Escherichia coli strains isolated from urine from long-term care facility residents in Cracow, Poland - Pobiega, Monika (International Scientific Literature, Inc., 2013)
BACKGROUND: The aim of this study was to assess the prevalence of multidrug-resistant Escherichia coli and extended-spectrum β-lactamases (ESBL) pathogens isolated from asymptomatic bacteriuria and urinary tract infections (UTIs), and the relationship between the phylogeny, antimicrobial resistance, and virulence among isolates in residents of 3 long-term care facilities (LTCF) in Krakow, Poland. MATERIAL/METHODS: This was point prevalence study and prospective infection control in a group of 217 people. Urine samples were examined with standard microbiological methods and screened for the presence of bla(CTX-M), bla(SHV,) and bla(TEM). E. coli isolates were screened for 6 common virulence factors (VFs) and classified according to the rapid phylogenetic grouping technique. RESULTS: Among all the strains tested, 14 isolates (13.9%) expressed ESBL activity. A significant proportion of isolates were resistant to ciprofloxacin (32.7%, n=33). Resistance to trimethoprim/sulfamethoxazole was identified among 45 isolates (44.5%). Independent risk factors for the presence of an ESBL-producing strain were: UTI, urinary and/or fecal incontinence, bedridden, and low values of the Barthel and Katz Indexes. Gene sequencing identified 8 bla(CTX-M-15), 1 bla(CTX-M-3), 9 bla(TEM-1,) and 1 bla(SHV-12). Among E. coli, no relationship between number of VF genes and phylogeny was found. The most prevalent virulence factor was fimH (82.1%). CONCLUSIONS: The findings of this study emphasize the need for further research on the epidemiology of multi-drug resistant organisms (MDRO) and ESBL in LTCF, including transmission patterns, rates of infection, and factors associated with infections. It may be necessary to extend the requirements and precautions to MDRO and ESBL-producers.